The relationship between Iranian women's perception of their birth team's compliance with medical ethics and their perception of labor pain - Parvin Yadollahi; Leila Bozorgian; Roksana Janghorban (BMC, 2024)
Abstract Background A safe and satisfactory childbirth experience with the least amount of pain constitutes one of the main domains of reproductive healthcare. The most important aspect of labor pain management is the moral and professional commitment of the health professionals and caregivers involved in creating a pleasant delivery. The present study examines the relationship between Iranian women's perceptions of their birth team's compliance with medical ethics and their perception of labor pain. Methods This cross-sectional study was conducted on 200 women opting for natural childbirth. The samples were selected by convenience sampling. Three questionnaires, including a demographic information questionnaire, the perception of labor pain questionnaire, and the medical ethics attitude in vaginal delivery questionnaire, were used to collect data. The data were entered into SPSS 22 and analyzed using correlation coefficient and multiple regression tests. The significance level for data analysis was set as less than 0.05. Results The results of the regression analysis showed that among the four principles of medical ethics, only the second and third principles (beneficence and non-maleficence) predicted the perception of labor pain (B = -0.267, P < 0.037). Among the different domains of these principles, the areas of giving the necessary information to the mother (B = -0.199, P = 0.001), respecting the mother's privacy (B = -0.194, P = 0.001), interaction with the mother (B = -0.287, P = 0.001) and assurance of fetal health (B = -0.492, P = 0.001) were predictors of labor pain perception score. Conclusions Compliance of the birth team with respecting the mother's privacy, having friendly interactions with the mother and giving fetal health assurance to the mother can be a predictor of the mother's decreased perception of labor pain.